Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1002/tera.1420130311
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medroxyprogesterone acetate on the maintenance of pregnancy in ovariectomized rats and rabbits

Abstract: Fetal survival, malformation rate, and fetal and placentd weights were examined near term in control rabbits, rabbits treated on day 6 with 5 mg of medroxyprogesterone acetate (MPA), a long acting progestin, and rabbits treated with 5 mg of MPA on day 6 and ovariectomized on day 7. MPA alone had no apparent effect on fetal or placental development but MPA plus ovariectomy increased fetal weight by 19% and placental weight by 60%. Fetal and placental development were examined near term in rats given similar tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Yochim andZarrow (1961} and have reported that placental overgrowth in ovariectomized rats is accompanied by small but significant increases in foetal weight, but Callard and Leathem (1971) did not observe any associated increases in foetal growth. Ovariectomy also induces placental overgrowth in the rabbit (Abdul-Karim et ale 1971; Bruce and Bartholomeusz 1976). However, it remains unclear whether this pheno-menon occurs in mammals other than the rat and rabbit, and the physiological significance of ovariectomy-induced placental overgrowth; in relation to the maintenance of gestation and foetal growth, is unknown (Callard and Leathem 1971;Chan and Leathem 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Yochim andZarrow (1961} and have reported that placental overgrowth in ovariectomized rats is accompanied by small but significant increases in foetal weight, but Callard and Leathem (1971) did not observe any associated increases in foetal growth. Ovariectomy also induces placental overgrowth in the rabbit (Abdul-Karim et ale 1971; Bruce and Bartholomeusz 1976). However, it remains unclear whether this pheno-menon occurs in mammals other than the rat and rabbit, and the physiological significance of ovariectomy-induced placental overgrowth; in relation to the maintenance of gestation and foetal growth, is unknown (Callard and Leathem 1971;Chan and Leathem 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Learner et al (1962) had similar results in the rat using a dose of 5 mg/kg of MPA, which is 80 times the HDE. Bruce and Bartholomeusz (1976) studied fetal survival, the malformation rate, and fetal and placental weights in pregnant rats and rabbits treated with MPA. In 28 pregnant rabbits, the malformation rate was not increased in the MPA-treated rabbits.…”
Section: Have Investigators Been Able To Develop a Teratogenic Animalmentioning
confidence: 99%